Pendampingan Pemanfaatan Canva AI dalam Pembuatan Media Infografis IPAS untuk Guru SD - Rohmatus Syafi’ah; Mukhammad Zainul Muttaqin; Rahyu Setiani; Alik Mustafidal Laili; Eka Yuliana Sari; Vindhy Dian Indah Pratika (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The rapid development of digital technology requires teachers to possess digital literacy and the ability to innovate in developing 21st-century learning media. This Community Service Program (PkM) focuses on enhancing the digital competence of teachers at Mulyosari 2 Elementary School, Tulungagung, through mentoring on the use of Artificial Intelligence (AI) features in Canva for designing Science and Social Studies (IPAS) infographic media. The program was conducted using a participatory action approach consisting of three stages: collaborative planning, intensive mentoring, and evaluation. The results show an improvement in teachers’ skills in utilizing Canva AI features such as Magic Write and Text to Image, as well as their ability to produce original, contextual, and efficient infographic designs. All participants successfully created at least one feasible infographic product, accompanied by increased motivation, confidence, and professional satisfaction. Overall, this activity contributes to strengthening teachers’ digital literacy and promoting technology-based learning innovation in elementary education.